“I attend at Vanguard and I attend here as well”: barriers to accessing healthcare services among older South Africans with HIV and non-communicable diseases - Lucia Knight; Enid Schatz; Ferdinand C. Mukumbang (International Journal for Equity in Health, 2018)
Abstract Background HIV and non-communicable disease (NCD) are syndemic within sub-Saharan Africa especially among older persons. The two epidemics interact with one another within a context of poverty, inequality and inequitable access to healthcare resulting in an increase in those aged 50 and older living with HIV and experiencing an NCD co-morbidity. We explore the challenges of navigating healthcare for older persons living with HIV and NCD co-morbidity. Methods In-depth semi-structured interviews were conducted with a small sample of older persons living with HIV (OPLWH). The perspectives of key informants were also sought to triangulate the evidence of OPLWH. The research took place in two communities on the outskirts of Cape Town, South Africa. All interviews were conducted by a trained interviewer and transcribed and translated for analysis. Thematic content analysis guided data analysis. Results OPLWH experienced an HIV-NCD syndemic. Our respondents sought care and accessed treatment for both HIV and other chronic (and acute) conditions, though these services were provided at different health facilities or by different health providers. Through the syndemic theory, it is possible to observe that OPLWH and NCDs face a number of physical and structural barriers to accessing the healthcare system. These barriers are compounded by separate appointments and spaces for each condition. These difficulties can exacerbate the impact of their ill-health and perpetuate structural vulnerabilities. Despite policy changes towards integrated care, this is not the experience of OPLWH in these communities. Conclusions The population living with HIV is aging increasing the likelihood that those living with HIV will also be living with other chronic conditions including NCDs. Thus, it is essential that health policy address this basic need to integrate HIV and NCD care.